THE USE OF TASK-BASED LEARNING TO ENHANCE ENGLISH ORAL PRESENTATION ABILITY AND SELF-CONFIDENCE OF 1ST YEAR STUDENTS, LAMPANG RAJABHAT UNIVERSITY - Poomchaiya, Pornchonnee (Journal of Education and Innovation, 2024)
The purposes of this research were to 1) study students’ English oral presentation ability after using task-based learning and 2) to compare students’ self-confidence before and after using task-based learning. The sample was 29 undergraduate students, Faculty of Education, who enrolled in the course “English Classroom Management” in the second semester of the academic year 2021 and was randomly selected by using cluster random sampling through the use of section as a unit of randomization. The research instruments consisted of 3 lesson plans using task-based learning, an English oral presentation ability evaluation form and self-confidence test. The data collected were analyzed with mean, standard deviation, and percentage. The findings were as follows: 1) the students’ English oral presentation ability increased after using task-based learning. The mean scores were 13.14, 14.71 and 16.14 and 2) the mean score of students’ self-confidence after using task-based learning was 3.72 which was higher than before using task-based learning. The mean score of students’ self-confidence before using task-based learning was 2.82.